2020
DOI: 10.1002/tal.1713
|View full text |Cite
|
Sign up to set email alerts
|

Seismic behavior of highly irregular structures with multiple passive energy dissipation system: Case study of a single‐column elevated station

Abstract: Summary This paper presents a case study of the layout strategy for a multiple passive energy dissipation (MPED) system and its influence on the seismic behavior of highly irregular structures. The investigated structure is a single‐column elevated station in a cantilevered structure form, which is unique and characterized by uneven mass and stiffness distributions in both elevation and plane. To improve seismic resistances of the focused structure, the MPED system composed of multiple types of passive energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The three sub-indices were averaged to obtain the index of the overall structure. The sub-index of the translation in the X direction, Er(X), can be calculated using Equation (8), where X i,BPA/NRHA denotes the displacement in the X direction at the mass center of the i th floor of the structure using the BPA or NRHA method. Similarly, the sub-index of the translation in the Y direction, Er(Y), can be calculated using Equation (9).…”
Section: Load Amplification Factor Adjustmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The three sub-indices were averaged to obtain the index of the overall structure. The sub-index of the translation in the X direction, Er(X), can be calculated using Equation (8), where X i,BPA/NRHA denotes the displacement in the X direction at the mass center of the i th floor of the structure using the BPA or NRHA method. Similarly, the sub-index of the translation in the Y direction, Er(Y), can be calculated using Equation (9).…”
Section: Load Amplification Factor Adjustmentmentioning
confidence: 99%
“…The composite structure system can effectively reduce the component size and realize multiple failure mechanisms in the vertical and horizontal directions, improving the seismic performance of complex station systems. Zhuang et al [8] applied multiple passive energy dissipation (MPED) devices to the vulnerable parts of the structure to improve its seismic performance. Nonlinear static and time-history analyses of the key substructure and entire structure revealed that the MPED system could effectively enhance the strength, stiffness, and ductility of the structure, reduce the general response significantly, and increase the energy dissipation capacity of the overall structure.…”
Section: Introductionmentioning
confidence: 99%